Delays in starting antiretroviral therapy in patients with HIV-associated tuberculosis accessing non-integrated clinical services in a South African township - Lawn, Stephen D (BioMed Central, 2011)
BACKGROUND: Delays in the initiation of antiretroviral therapy (ART) in patients with HIV-associated tuberculosis (TB) are associated with increased mortality risk. We examined the timing of ART among patients receiving care provided by non-integrated TB and ART services in Cape Town, South Africa. METHODS: In an observational cohort study, we determined the overall time delay between starting treatment for TB and starting ART in patients treated in Gugulethu township between 2002 and 2008. For patients referred from TB clinics to the separate ART clinic, we quantified and identified risk factors associated with the two component delays between starting TB treatment, enrolment in the ART clinic and subsequent initiation of ART. RESULTS: Among 893 TB patients studied (median CD4 count, 81 cells/μL), the delay between starting TB treatment and starting ART was prolonged (median, 95 days; IQR = 49-155). Delays were shorter in more recent calendar periods and among those with lower CD4 cell counts. However, the median delay was almost three-fold longer for patients referred from separate TB clinics compared to patients whose TB was diagnosed in the ART clinic (116 days versus 41 days, respectively; P < 0.001). In the most recent calendar period, the proportions of patients with CD4 cell counts < 50 cells/μL who started ART within 4 weeks of TB diagnosis were 11.1% for patients referred from TB clinics compared to 54.6% of patients with TB diagnosed in the ART service (P < 0.001). CONCLUSIONS: Delays in starting ART were prolonged, especially for patients referred from separate TB clinics. Non-integration of TB and ART services is likely to be a substantial obstacle to timely initiation of ART.